FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN STATUS GIZI PADA ANAK BALITA DI LINGKUNGAN 15 KELURAHAN PEKAN LABUHAN - Pahala Maringan Jubel Simangunsong (Fakultas Kesehatan Masyarakat Universitas Prima Indonesia, 2020)
ABSTRACTNutrition status is health relating to the use of eating pattern by body. Belawan Public Health center ranked4 with malnutrition status with the total of 196 (3.1%) below Medan Labuhan, Medan Helvetia, and MedanTuntungan. Malnutrition mostly occured at environment 15 that is, 8 babies suffering from malnutrition outof 2.047 babies, and 2 babies having bad nutrition. The research aims at finding out the relationshipbetween dependent and independent variables at environment 15, families of Pekan Labuhan, PekanLabuhan regency of Medan Labuhan in 2015. The research method is Cross sectional using total samplingtechniqe that 40 familes were taken as samples having babies. The research data were taken byperforming home visits from house to house, visiting to integrated post service (Posyandu) with interviewguide and questionnaires. The result of the study showed that 2 respondents (5%) experiencedmalnutrition, 8 respondents (20%) suffered from less nutrition and 30 respondents (75%) experiencedgood nutrition. Based on bivariate analysis, it was found that there was a dependent variable not having asignificant relationship with baby nutrition status; that is, variable of family income ( ρ-value = 0.108) and 4independent variables have a significant relationship with baby nutrition status; that is, variable of mother’s(ρ-value = 0.000), and the number of family member (ρ-value = 0.027). The research concludes that thereis a significant relationship between mother knowledge, mother attitude, mother education and the numberof family members on the baby nutrition status. Public Health Center is suggested to provide counseling tomothers having babies continually Mothers are suggested to visit Public Health Center routinely to checkup their baby nutrition